PENGATURAN DAYA ANTARA PHOTOVOLTAIC DAN BATERAI DALAM SMART GRID - Elfira Pranita; Muhammad Suharto; Made Andik Setiawan; Eko Sulistyo (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
The output of photovoltaic is highly dependent on the intensity of sunlight. When the sunlight intensity received by photovoltaic matches or more than the specified, the photovoltaic can produce the maximum output according to the specifications. However, if the intensity is less than specification, the photovoltaic output will be less than expected. This can happen on cloudy days or in the morning, evening or night. Meanwhile, load electric power requirements may varies, it does not depend on time or weather. So that at that time the supply of electrical power needed by the load must be supplied by other energy producer, such as battery. Conversely, when photovoltaic generate maximum electrical power or more than the load requirement, more electrical energy can be stored by the battery. To be able to do this, a device must be designed that can regulate the amount of power output from the photovoltaic or battery. The photovoltaic or battery output power setting is adjusting the pulse width modulation (PWM) signal via a controller, namely Arduino MEGA 2560. This power setting works by utilizing a DC-DC converter, buck-boost converter type XL6019. Experiments were carried out experimentally and measured directly. Based on the measurement results, photovoltaic power has been able to supply the load's electrical power needs with a light intensity of 50% of the required specifications. The experimental results show that the proportion of power absorbed or discharged by the battery can be adjusted according to the photovoltaic output power to the load requirements.